Assessing Designers’ Perception, Analysis, and Reflective Using Verbal Protocol Analysis - Muhammad Jameel, Mohamed Kamil; Shahriman, Zainal Abidin; Oskar, Hasdinor Hassan (Springer Nature Singapore Pte Ltd, 2019)
This paper examines designers’ response toward the theory of uncon- scious interaction and cognitive of human behavior in the everyday product. During the Verbal Protocol Analysis (VPA) study, 30 designers were given four selected images which have been categorized into four attributes of unconscious interaction in everyday human behavior. At the same time, they were asked to verbally respond to following aspects: (1) their perception toward the attributes of the unconscious interaction of human behavior in everyday life; (2) their analysis on the given images; and (3) their reflection of those given images. The contribution of the study led to the identification of designers’ abilities to perceive, understand, analyze, and reflect in enhancing the value of an existing product by interpreting the design needs from the four attributes of unconscious interaction in everyday human behavior.